Natural Resources and International Labour Mobility - Romero, J (Routledge, 2016)
We study the relationship between natural resource wealth and (skilled and unskilled) emigration. The source data for international migration rates come from Brücker, Capuano, and Marfouk (2013) and measures of resource wealth from the World Bank database. We find that natural resource abundance reduces skilled emigration regardless of countries’ natural wealth, but that natural resources reduce unskilled emigration only in resource-rich countries. © 2016 Taylor & Francis.